2010
DOI: 10.1111/j.1745-4549.2008.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF TEMPERATURE AND MODIFIED ATMOSPHERE ON QUALITY PRESERVATION OF SAYER DATE FRUITS (PHOENIX DACTYLIFERAL.)

Abstract: Sayer date fruits were stored by different preservation techniques including high carbon dioxide modified atmosphere packaging (MAP), cool storage and freezing for 150 days. The effects of these treatments on several quality factors of the fruits were investigated. Control package samples (kept at 30C without atmosphere modification) had the highest number of live insects as well as yeast and mold colony counts (P < 0.05). pH values of the MAP samples stored at 30C were less than the other treatments. Water ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 20 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…Similarly, Dehghan-Shoar et al [17] reported that modified atmosphere packaging with higher CO 2 slowed down the growth of yeasts and moulds of sayer date palm fruit stored at 4°C. On the other hand, the higher growth level of yeasts and moulds compared to that of MAB might be due to the high tolerance of yeasts and moulds to the acidic conditions compared to bacteria [18,19].…”
Section: Mesophilic Aerobic Bacteria (Mab) Yeasts and Mouldsmentioning
confidence: 93%
“…Similarly, Dehghan-Shoar et al [17] reported that modified atmosphere packaging with higher CO 2 slowed down the growth of yeasts and moulds of sayer date palm fruit stored at 4°C. On the other hand, the higher growth level of yeasts and moulds compared to that of MAB might be due to the high tolerance of yeasts and moulds to the acidic conditions compared to bacteria [18,19].…”
Section: Mesophilic Aerobic Bacteria (Mab) Yeasts and Mouldsmentioning
confidence: 93%
“…Effects of chemicals, controlled atmospheres and physical methods have been investigated (Chao and Krueger ; Dehghan‐Shoar et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…The effects of MAP in maintaining quality and extending shelf life of fresh and dried dates as well as some date products have been reported in the literature. Dehghan-Shoar et al (2010) compared the effects of MAP under high CO 2 on the quality of Sayer dates fruits with low temperature storage and freezing. The results showed that MAP with 85% CO 2 + 3% O 2 and 75% CO 2 + 12% O 2 maintained the best quality of dates with no physiological disorder, and off-odor and off-flavor throughout the 150-day storage.…”
Section: Modified Atmosphere Packagingmentioning
confidence: 99%
“…The visual appearance of control and treated dates is shown in Figure 6.7. High CO 2 MAP has also shown to be effective in eliminating insects in stored dates (Dehghan-Shoar et al 2010). Al-Redhaiman (2004) also reported that storage under high CO 2 atmosphere extended the shelf life of Barhi date fruits.…”
Section: Modified Atmosphere Packagingmentioning
confidence: 99%